2017
DOI: 10.1111/ijcp.12927
|View full text |Cite
|
Sign up to set email alerts
|

Soft drink intake and the risk of metabolic syndrome: A systematic review and meta-analysis

Abstract: Sugar-sweetened beverage and ASB intake are both associated with metabolic syndrome. This association may be driven by the fact that soft drink intake serves as a surrogate for an unhealthy lifestyle, or an adverse cardiovascular risk factor profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…The cluster of cardiometabolic risk factors associated with intake of sugar-sweetened beverages in the present study were those that form the criteria for metabolic syndrome. This is consistent with findings from cross-sectional studies that have suggested an association between sugar-sweetened beverage intake and metabolic syndrome, although this has not consistently been observed in prospective studies [29].…”
Section: Discussionsupporting
confidence: 90%
“…The cluster of cardiometabolic risk factors associated with intake of sugar-sweetened beverages in the present study were those that form the criteria for metabolic syndrome. This is consistent with findings from cross-sectional studies that have suggested an association between sugar-sweetened beverage intake and metabolic syndrome, although this has not consistently been observed in prospective studies [29].…”
Section: Discussionsupporting
confidence: 90%
“…A more detailed questionnaire should be used in the future. Furthermore, data on some behaviors (such as alcohol consumption) are based on self-declaration with the possibility of misclassification of exposure due to underreporting (76)(77).…”
Section: Discussionmentioning
confidence: 99%
“…Persons with MetS have an increased risk of death from all causes as well as CVD (4)(5)(6)(7)(8) . Increasing evidence indicates that MetS is affected by genetic (9,10) and lifestyle factors, such as alcohol consumption, soft drink intake, coffee consumption and sedentary behaviours (11)(12)(13)(14) . As the two important determinants of body weight, diet and physical activity can influence obesity and most of the MetS components directly (15) .…”
mentioning
confidence: 99%